POMBOX: A Fission Yeast Cloning Toolkit for Molecular and Synthetic Biology - Hebra, Téo; Smrčková, Helena; Elkatmis, Büsra; Převorovský, Martin; Pluskal, Tomáš (ACS synthetic biology, 2024)
The fission yeast Schizosaccharomyces pombe is a popular model organism in molecular biology and cell physiology. With its ease of genetic manipulation and growth, supported by in-depth functional annotations in the PomBase database and genome-wide metabolic models,S. pombe is an attractive option for synthetic biology applications. However,S. pombe currently lacks modular tools for generating genetic circuits with more than 1 transcriptional unit. We developed a toolkit to address this gap. Adapted from the MoClo-YTK plasmid kit for Saccharomyces cerevisiae and using the same modular cloning grammar, our POMBOX toolkit is designed to facilitate fast, efficient, and modular construction of genetic circuits inS. pombe. It allows for interoperability when working with DNA sequences that are functional in bothS. cerevisiae and S. pombe (e.g., protein tags, antibiotic resistance cassettes, and coding sequences). Moreover, POMBOX enables the modular assembly of multigene pathways and increases the possible pathway length from 6 to 12 transcriptional units. We also adapted the stable integration vector homology arms to Golden Gate assembly and tested the genomic integration success rates depending on different sequence sizes, from 4 to 24 kb. We included 14 S. pombe promoters that we characterized using two fluorescent proteins, in both minimally defined (EMM2─Edinburgh minimal media) and complex (YES─yeast extract with supplements) media. Then, we examined the efficacy of 6 S. cerevisiae and 6 synthetic terminators in S. pombe. Finally, we used the POMBOX kit for a synthetic biology application in metabolic engineering and expressed plant enzymes in S. pombe to produce specialized metabolite precursors, namely, methylxanthine, amorpha-4,11-diene, and cinnamic acid from the purine, mevalonate, and aromatic amino acid pathways.
Keywords: genomic integration; Schizosaccharomyces; toolkit; Saccharomyces cerevisiae; Synthetic Biology; syntetická biologie; Golden Gate; Plasmids; MoClo; Schizosaccharomyces pombe; plazmidy; plasmid; Cloning, Molecular; klonování DNA